Pengaruh Pariwisata pada adaptasi fungsi, bentuk dan ruang arsitektur puri, Studi kasus: Puri Saren Agung Ubud - Rachmat Budihardjo (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
The effect of tourism on function adaptation, forms and space of puri architecture, a case study: at Puri Saren Agung Ubud Balinese traditional architecture is an architecture that grows and develops in the midst of its people. Efforts to safeguard Balinese culture (including its architecture) as a magnet (tourism) of attraction have been carried out since the Dutch Colonial government as